Vasomotor responses to the Valsalva manoeuvre in normal subjects and in patients with diabetes mellitus. Issue 4 (October 1979) - Bennett, T; Hosking, D J; Hampton, J R
Abstract : Cardiovascular responses to the Valsalva manoeuvre were examined in 19 non-diabetic subjects and 32 diabetic patients, some with signs of autonomic dysfunction. All the non-diabetic subjects showed an overshoot in systemic arterial pressure and a bradycardia after the manoeuvre, and in 11 of them only forearm vasoconstriction occurred. However, in eight non-diabetic subjects a forearm vasodilatation was observed at some stage after the Valsalva manoeuvre. Similar patterns of vasomotor responses were seen in some of the diabetic patients. However, those diabetics with postural hypotension showed a systemic arterial hypotension after the Valsalva manoeuvre with no significant change in forearm vascular resistance. Such a response is abnormal but forearm vasodilatation alone may not be.